Trade-off curves applications to support set-based design of a surface jet pump - Araci, Zehra Canan; Al-Ashaab, Ahmed; Lasisz, Piotr W.; Flisiak, Jakub W.; Mohd Maulana, Muhd I. I.; Beg, Najam; Rehman, Abdullah (Elsevier, 2017)
Knowledge has become the most important asset of companies, especially in improving their product development processes. The set-based design approach is an efficient way of designing high quality, optimised designs. However, it requires a proven knowledge environment. Trade-off curves (ToCs) have the capability of providing the right knowledge and displaying it in a visual form. Although there are a few applications of ToCs that have recently been published in the literature, none of them demonstrates an integrated implementation of ToCs throughout the SBCE process. This paper presents the integrated use of ToCs, based on both physics-knowledge and proven knowledge, in order to compare and narrow down the design-set and to achieve an optimal design solution. These are key activities of the SBCE process model. Since an accurate, documented and visual knowledge environment is created by the use of ToCs within SBCE, the integrated approach proposed in this paper plays a vital role in eliminating the need for prototyping and testing at the early stages of product development. The integrated approach was implemented in an industrial case study for a surface jet pump. Surface jet pumps are used to increase the production rate of low-pressure oil/gas wells. It has been found that through ToCs, the conflicting relationships between the characteristics of the product can be understood and communicated effectively among the designers. This facilitated the decision-making on an optimal design solution in a remarkably short period of time. Furthermore, the surface jet pump resulting from the case study achieved an increase of the oil/gas production by nearly 60%.
Keywords: lean product development; set-based concurrent engineering; trade-off curves; creating knowledge; visual knowledge; oil and gas production; surface jet pump